Adhesion of Individual Attachment Setae of the Spider Cupiennius salei to Substrates With Different Roughness and Surface Energy - Poerschke, Bastian; Gorb, Stanislav N.; Schaber, Clemens F. (Frontiers in Mechanical Engineering, 2021)
Dynamic adhesion is a key ability for animals to climb smooth surfaces. Spiders evolved, convergent to geckos, a dry adhesive system made of setae branching into smaller microtrichia ending as spatulae. Several previous studies concentrated either on the whole adhesive claw tuft on the spider´s foot that consists of attachment setae or on the single adhesive contact elements, the microtrichia with spatula-shaped tips. Here, the adhesion of single setae of the spider Cupiennius salei was examined and the morphology of the pretarsus and the fine structure of the setae were studied in further detail. Using individual setae fixed to force sensing cantilevers, their adhesion at different contact angles with a glass substrate was measured as well as their adhesive performance on substrates with different roughness and on smooth surfaces with different surface energies. The results show an individual variability of the adhesive forces corresponding to the seta morphology and especially to the seta tip shape. The tip shapes of the setae vary largely even in neighboring setae of the pretarsal claw tuft that comprises approximately 2,400 setae. Regarding surface energy of the substrate, the adhesion force on hydrophobic polytetrafluoroethylene was 30% of that on a hydrophilic glass substrate, which points to the importance of both van der Waals interactions and hydrogen bonds in spider adhesion.